2019
DOI: 10.1111/ijfs.14410
|View full text |Cite
|
Sign up to set email alerts
|

Anion exchange polymeric sorbent coupled to high‐performance liquid chromatography with UV diode array detection for the determination of ten N‐nitrosamines in meat products: a validated approach

Abstract: Summary Among mechanisms and molecules presumably involved in the carcinogenicity induced by meat consumption, the N‐nitrosamines (N‐NAs) are a class of compounds characteristic of processed meats. In this work, an analytical method for the determination of ten N‐nitrosamines (N‐nitrosomorpholine, N‐nitrosomethylethylamine, N‐nitrosopyrrolidine, N‐nitrosodiethylamine, N‐nitrosopiperidine, N‐nitrosodipropylamine, N‐nitrosodimethylaniline, N‐nitrosodibutylamine, N‐nitrosodiphenylamine and N‐nitrosodibenzylamine)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The most common nitrosating agents of food are nitrite salts and nitrogen oxides. Although the most representative type of food linked to this risk is processed meat [ 14 ], several authors also reported the presence of different N-nitrosamines in vegetables, such as pickled and fermented vegetables. More in-depth, these authors quantified levels of N-nitrosodimethylamine and N-nitrosopyrrolidine at concentrations up to 15 and 25.5 µg kg −1 , respectively [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common nitrosating agents of food are nitrite salts and nitrogen oxides. Although the most representative type of food linked to this risk is processed meat [ 14 ], several authors also reported the presence of different N-nitrosamines in vegetables, such as pickled and fermented vegetables. More in-depth, these authors quantified levels of N-nitrosodimethylamine and N-nitrosopyrrolidine at concentrations up to 15 and 25.5 µg kg −1 , respectively [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding non‐volatile N‐ NAs, some analytical approaches have used high‐performance liquid chromatography (HPLC) with UV, fluorescence and mass spectrometry detection. All these techniques have also been applied for the simultaneous determination of volatile and non‐volatile N‐ NAs in food and other matrices (Komarova and Velikanov, 2001 ; Wang et al, 2006 ; Avasilcai et al, 2014 ; Li et al, 2018 ; Iammarino et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative analysis of NAs is usually performed on the chromatography coupled to high‐sensitive and selective detectors 7 . Liquid chromatography (LC) coupled with photo‐diode array, fluorescence, mass spectrometry (MS) and tandem mass spectrometry (MS/MS) detectors has been employed for quantification 8‐9 . Moreover, gas chromatography (GC) coupled with a nitrogen phosphorus detector, a thermal energy analyzer, MS and tandem MS (MS/MS) are also employed as a detection method for determining NAs in foodstuffs 10‐11 .…”
Section: Introductionmentioning
confidence: 99%
“…7 Liquid chromatography (LC) coupled with photo-diode array, fluorescence, mass spectrometry (MS) and tandem mass spectrometry (MS/MS) detectors has been employed for quantification. [8][9] Moreover, gas chromatography (GC) coupled with a nitrogen phosphorus detector, a thermal energy analyzer, MS and tandem MS (MS/MS) are also employed as a detection method for determining NAs in foodstuffs. [10][11] In addition, the abundance of the molecular mass ion could be significantly enhanced when the GC-MS/MS was equipped with chemical ionization and operated in positive mode.…”
Section: Introductionmentioning
confidence: 99%